1994
DOI: 10.1104/pp.105.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Nonvascular, Symplasmic Diffusion of Sucrose Cannot Satisfy the Carbon Demands of Growth in the Primary Root Tip of Zea mays L

Abstract: Nonvascular, symplasmic transport of sucrose (Suc) was investigated theoretically in the primary root tip of maize (Zea mays 1.cv WF9 x Mo 17) seedlings. Symplasmic diffusion has been assumed to be the mechanism of transport of Suc to cells in the root apical meristem (R.T. Ciaquinta, W. Lin, N.L. Sadler, V.R. Franceschi [1983] Plant Physiol 72: 362-367), which grow apical to the end of the phloem and must build all biomass with carbon supplied from the shoot or kernel. We derived an expression for the growths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
77
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(82 citation statements)
references
References 61 publications
5
77
0
Order By: Relevance
“…In the roots, GUS staining was restricted to the very tips, probably to the root meristem. It has been shown for maize that symplastic diffusion of sugars from the veins toward the primary root tips cannot satisfy the carbon demand of the growing root meristem (Bret-Harte and Silk, 1994). Expression of STP4 mRNA in this tissue could indicate a similar situation for Arabidopsis.…”
Section: Sink-specific Expression Of Stp4mentioning
confidence: 97%
“…In the roots, GUS staining was restricted to the very tips, probably to the root meristem. It has been shown for maize that symplastic diffusion of sugars from the veins toward the primary root tips cannot satisfy the carbon demand of the growing root meristem (Bret-Harte and Silk, 1994). Expression of STP4 mRNA in this tissue could indicate a similar situation for Arabidopsis.…”
Section: Sink-specific Expression Of Stp4mentioning
confidence: 97%
“…The phloem develops closer to the root tip than the xylem and channels water from the mature regions into the growth zone (Bret-Harte and Silk, 1994;Frensch and Hsiao, 1995;Pritchard, 1996;Pritchard et al, 2000). We assume the following.…”
Section: Assumptionsmentioning
confidence: 99%
“…The nodal roots grow through air and then dry layers of surface soil, making it unlikely that the expanding root cells obtain water from the dry media surrounding the root. Empirical and theoretical studies have concluded that the phloem probably provides water for growth of the primary maize root (Bret-Harte and Silk, 1994;Frensch and Hsiao, 1995;Pritchard, 1996;Pritchard et al, 1996Pritchard et al, , 2000Hukin et al, 2002;Gould et al, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While the mechanisms of Suc loading into the phloem have been intensively studied over a similar time period (Riesmeier et al, 1993(Riesmeier et al, , 1994Bü rkle et al, 1998;Meyer et al, 2004;Sauer et al, 2004), those by which it is unloaded into the sink organ have only been clarified relatively recently and only for a subset of plants studied (Bret-Harte and Silk, 1994;Viola et al, 2001;Kü hn et al, 2003;Carpaneto et al, 2005). In the tomato (Solanum lycopersicum) fruit, the path of Suc unloading remains somewhat contentious (Ruan and Patrick, 1995;Hackel et al, 2006).…”
mentioning
confidence: 99%